SISTEM INFORMASI NILAI AKADEMIK MAHASISWA BERBASIS WEB PADA SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER SAMARINDA - Sumarni, Sumarni; Haerullah, Haerullah; Sugiyono, Sugiyono (DiJITAC : Digital Journal of Information Technology and Communication, 2020)
As the College First in Samarinda STMIK SAMARINDA have a vision Become Leading Universities in the Field of Information and Computer Employers' The vision of East Kalimantan IN 2022 WITH the realization of human beings The Smart And devoted shown to God Almighty. In the Value Data Processing HAL students STMIK SAMARINDA Often Occur Technical constraints such as AT Processing Values When a student, where the student is very difficult to review determine PT Values What they earn. Singer constraints occurred BECAUSE Processing Data Value Still conventional students. Article Search Google know the problems of singer, so rare for a review should be taken MAKE AN Information System Web-based academic value ON STMIK SAMARINDA. Purpose of holding study is to review identifies Systems Information Values Academic STMIK SAMARINDA The Walk, Finding Data will be processed relates WITH Systems Information Values academic STMIK SAMARINDA WITH using the programming language PHP and MySQL, the data is studied Yang collected for the review prepared Become A Structure Data Regularly accordance WITH System will be Created. Benefits That You Want accomplished singer Research hearts is to review design a Value-Based Academic Information System web ON College of Management Information and Computer STMIK SAMARINDA, to facilitate the review of academic parties STMIK SAMARINDA hearts information serves students' academic value Operative Quickly And Accurately.Searching Google Pages Information System Academic Value STMIK SAMARINDA The web-based parties can be easier for academic administration, especially hearts Processing Values, and also can be improve the performance Operate Fast And Accurate information.